Influence of fiber on glycemic index of enteral nutrition - Visek, Jakub; Zourek, Michal; Lacigova, Silvie; Rusavy, Zdenek (JPEN. Journal of parenteral and enteral nutrition, 2007)
BACKGROUND: Enteral nutrition is indicated in patients with malnutrition due to inadequate peroral intake. A number of these patients have diabetes mellitus or impaired glucose tolerance. The aim of the study was to evaluate the influence of fiber-enriched enteral nutrition on postprandial glycemia and insulinemia. METHODS: Ten healthy volunteers consumed the following solutions: A. 50 g of glucose, B. enteral formula containing 50 g of saccharides, and C. enteral formula containing 50 g of saccharides enriched with 2.3 g of fiber/100 mL. Postprandial glycemia and insulinemia were measured in time period after administration of specified nutrition. Time courses of glycemia and insulinemia were used for calculation of areas under the curve (AUC). The glycemic (GlyI) and insulinemic (InsI) indices of the nutrition were subsequently derived from AUC. Every measurement was performed 3 times for given type of nutrition. RESULTS: Results are presented as median and interquartile range. GlyI of enteral nutrition was 85.76 (82.71-87.82), GlyI of enteral nutrition with fiber was 84.61 (80.31-94.39). InsI of enteral nutrition was 114.15 (106.55-137.71); InsI of enteral nutrition with fiber was 104.10 (96.71-127.96). The GlyI and InsI results did not differ significantly. Addition of fiber into enteral nutrition did not influence postprandial glycemia in comparison with common enteral nutrition. CONCLUSIONS: Added fiber in polymerous enteral nutrition does not influence postprandial glycemia compared with polymerous enteral nutrition without fiber.
Keywords: Glycemic Index; Insulin; diabetes mellitus; Diabetes Mellitus; Dietary Fiber; hyperglykemie; Hyperinsulinism; Male; potravní vláknina; glykemický index; inzulin; klinické křížové studie; krevní glukóza; Adult; dospělí; mužské pohlaví; postprandiální období; hyperinzulinismus; potrava speciální; Enteral Nutrition; Hyperglycemia; plocha pod křivkou; Malnutrition; lidé; ženské pohlaví; Humans; Postprandial Period; Area Under Curve; podvýživa; Food, Formulated; Cross-Over Studies; Female; Blood Glucose; enterální výživa